Toy collections in private preschools in Marikina City management policies and practices - Orocay, Anna Liza G. (2007)
More and more libraries are incorporating toys in their collection today. Mainly, this study aims to examine the management policies and practices of toy collections in preschool libraries, specifically, the organization and arrangement of toys in the collection, policies and practices on collection development, as well as the utilization and maintenance of the toy collection. From the documentation of management practices and policies of different libraries involved, this study will provide guidelines and insights to improve the management of the toy collection in a library, thus providing ways to better serve its users.